Transgenic Cotton Plants Expressing Cry1Ia12 Toxin Confer Resistance to Fall Armyworm (Spodoptera frugiperda) and Cotton Boll Weevil (Anthonomus grandis) - de Oliveira, Raquel S.; Oliveira-Neto, Osmundo B.; Moura, Hudson F. N.; de Macedo, Leonardo L. P.; Arraes, Fabrício B. M.; Lucena, Wagner A.; Lourenço-Tessutti, Isabela T.; de Deus Barbosa, Aulus A.; da Silva, Maria C. M.; Grossi-de-Sa, Maria F. (Frontiers in Plant Science, 2016)
Gossypium hirsutum (commercial cooton) is one of the most economically important fibers sources and a commodity crop highly affected by insect pests and pathogens. Several transgenic approaches have been developed to improve cotton resistance to insect pests, through the transgenic expression of different factors, including Cry toxins, proteinase inhibitors, and toxic peptides, among others. In the present study, we developed transgenic cotton plants by fertilized floral buds injection (through the pollen-tube pathway technique) using an DNA expression cassette harboring the cry1Ia12 gene, driven by CaMV35S promoter. The T0 transgenic cotton plants were initially selected with kanamycin and posteriorly characterized with PCR and Southern blot experiments to confirm the genetic transformation. Western blot and ELISA assays indicated the transgenic cotton plants with higher Cry1Ia12 protein expression levels to be further tested in the control of two major G. hirsutum insect pests. Bioassays with T1 plants revealed the Cry1Ia12 protein toxicity on Spodoptera frugiperda larvae, as evidenced by mortality up to 40% and a significant delay in the development of the target insects compared to untransformed controls (up to 30-fold). Also, a significant reduction of Anthonomus grandis emerging adults (up to 60%) was observed when the insect larvae were fed on T1 floral buds. All the larvae and adult insect survivors on the transgenic lines were weaker and significantly smaller compared to the non-transformed plants. Therefore, this study provides GM cotton plant with simultaneous resistance against the Lepidopteran (S. frugiperda) and the Coleopteran (A. grandis) insect orders, and all data suggested that the Cry1Ia12 toxin could effectively enhance the cotton transgenic plants resistance to both insect pests.